2013
DOI: 10.1007/8904_2013_273
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Metabolic Control in Adolescents and Young Adults with Phenylketonuria: Self-Imposed Protein Restriction May Be Harmful

Abstract: Background: In untreated patients, phenylketonuria (PKU) results in severe encephalopathy with mental retardation. A protein-restricted diet is recommended which can be relaxed in adolescence/adulthood.Methods: We contacted all 72 adult/adolescent PKU patients who had been treated in our center during early childhood. Some still regularly attended our outpatient clinics, while others were lost for follow-up, giving 51 patients in our study. We asked all patients to complete a dietary protocol as well as a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
(44 reference statements)
3
22
0
Order By: Relevance
“…The advised upper limit in Switzerland is 600 μmol/L, which is in accordance with the recently published European guideline [6]. However, many patients with good Phe control in childhood and adolescence will have difficulties to maintain a rigid diet in adulthood [7,8,9,10]. Adults often find it difficult to integrate a strict diet, including regular AAM intake, into social and professional life.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The advised upper limit in Switzerland is 600 μmol/L, which is in accordance with the recently published European guideline [6]. However, many patients with good Phe control in childhood and adolescence will have difficulties to maintain a rigid diet in adulthood [7,8,9,10]. Adults often find it difficult to integrate a strict diet, including regular AAM intake, into social and professional life.…”
Section: Introductionmentioning
confidence: 77%
“…This study represents the typical situation and real-life setting of an adult PKU clinic, where many patients who stay in regular follow-up principally remain on treatment, but relax their diet (restriction of natural protein, AAM intake) to a variable degree [8,9]. Commonly, patients reduce the amount of AAM, but maintain some dietary protein restriction.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported abnormalities despite the fact that all patients had adhered to dietary treatment since birth . Additionally, the severity of brain abnormalities were generally associated with historical Phe levels, while there appeared to be no relationship with Phe concentration at the time of MRI evaluation . Furthermore, there was no significant correlations between the volumes of different brain structures and current or historical Phe levels…”
Section: Neuroimagingmentioning
confidence: 96%
“…Average Phe levels have been reported to be significantly correlated with scores for psychoticism and psychiatric symptom intensity, while better Phe control during childhood was associated with better mood during adulthood . Similarly, depression and anxiety scores were positively correlated with the age at diet initiation and childhood Phe levels, respectively .…”
Section: Psychiatric Mood and Behavioral Outcomesmentioning
confidence: 97%
See 1 more Smart Citation